The The Relationship of Job Satisfaction and Work Motivation to Turnover Intention with Employee Engagement as an Intervening Variable: The Relationship of Job Satisfaction and Work Motivation to Turnover Intention with Employee Engagement as an Intervening Variable - Malik, Ahmad Malik; Violinda, Qristin; Setiawati, Ira (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study aims to examine the factors that affect turnover intention in PT Mitra Pengusaha Indonesia where the turnover intention rate is quite high. This study examines the variables that affect turnover intention through job satisfaction, work motivation, and employee engagement. The population and sample of this study are employees of PT Mitra Pengusaha Indonesia, the sample in this study is 286 people. The sample collection method uses the Probability Sampling technique using the simple random sampling method. The data collection method was carried out by distributing a questionnaire measured with 44 indicators using the Likert scale. The data analysis technique uses the Partial Least Square - Structural Equation Model (PLS-SEM). The test results showed that job satisfaction, work motivation and employee engagement had an effect on turnover intention. In addition, employee engagement is influential and can be a mediator between job satisfaction and work motivation on turnover intention.